2022
DOI: 10.1073/pnas.2113628119
|View full text |Cite
|
Sign up to set email alerts
|

Bats host the most virulent—but not the most dangerous—zoonotic viruses

Abstract: Significance The clear need to mitigate zoonotic risk has fueled increased viral discovery in specific reservoir host taxa. We show that a combination of viral and reservoir traits can predict zoonotic virus virulence and transmissibility in humans, supporting the hypothesis that bats harbor exceptionally virulent zoonoses. However, pandemic prevention requires thinking beyond zoonotic capacity, virulence, and transmissibility to consider collective “burden” on human health. For this, viral discovery… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 63 publications
0
39
0
Order By: Relevance
“…Many studies have confirmed a host-parasite relationship between bats and a myriad of viral pathogens. Bat viruses have disrupted global health and economies because of their virulence relative to other mammalian and avian reservoirs [ 1 , 2 ]. Zoonotic virus diversity within the Indian flying fox ( Pteropus medius, previously known as Pteropus giganteus ) population has been previously reported, including highly virulent and pathogenic viruses such as flaviviruses, henipavirus, coronaviruses and hantaviruses [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have confirmed a host-parasite relationship between bats and a myriad of viral pathogens. Bat viruses have disrupted global health and economies because of their virulence relative to other mammalian and avian reservoirs [ 1 , 2 ]. Zoonotic virus diversity within the Indian flying fox ( Pteropus medius, previously known as Pteropus giganteus ) population has been previously reported, including highly virulent and pathogenic viruses such as flaviviruses, henipavirus, coronaviruses and hantaviruses [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that the number of zoonotic viruses found in mammalian orders is proportional to the number of species of each respective order, suggesting that bats are not special pathogen reservoirs and that they host a large diversity of viruses because of their high species diversity ( 16 ). There is still no consensus if bats do carry and spread more human-pathogenic viruses than other mammalian orders ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bats (order: Chiroptera) make up an extremely diverse mammalian order that has been identified as a reservoir of many of the world's most virulent zoonotic viruses [1][2][3] . Bats' capacity to host virulent zoonotic viruses without experiencing disease is posited to be a byproduct of their evolution of flight, which necessitated metabolic adaptations leading to both elongated lifespans and immune system modifications promoting the evolution of viruses that are virulent to non-bat hosts 1,[4][5][6] .…”
Section: Introductionmentioning
confidence: 99%